Media optimization for bioproteins production from cheaper carbon source - Jamal, Parveen; Alam, Md. Zahangir; Salleh, N. U. (School of Engineering, Taylor’s University College, 2008)
There are high demands for animal and human food supply especially protein, which is an important dietary component. Agricultural wastes, cheap carbon sources- which are rich and have high energy, can be used for producing the value added bioprotein. A lab scale study was carried out to optimize the media composition for bioprotein production from a cheaper carbon source - wheat flour using potential strain, which was selected earlier by screening different microorganisms. The performance of the selected strain was enhanced by media optimization with varied substrate concentration, nitrogen sources and nutrient supplementation according to the central composite design from STATISTICA software. Statistical optimization was carried out to evaluate the polynomial regression model through effect of linear, quadratic and interaction of the factors. The maximum biomass produced was 21.89 g/L with optimum fermentation conditions of wheat flour (4 g/L), nitrogen concentration (0.5 g/L), nutrient concentration (0.1 g/L), and four days of fermentation.